PENYULUHAN PERANAN PENGELOLAAN DAN PARTISIPASI ANGGOTA TERHADAP PERKEMBANGAN KOPERASI UNIT DESA - Surahman Surahman (AGRITEXTS: Journal of Agricultural Extension, 2004)
Cooperation belong to its members who are also its customer. Beside it also belongs to the stockholders. Things that are sometimes forgotten in the detail information about cooperation are: The involvement of the members in many aspects such as: the existence of the cooperation, its type, the management, the service and the reason why the become the members, the members play an important role in the increase and the decrease of the cooperation. The cooperation demands the professionalism of the managers and the consequense that the cooperation should also the economic spirit. KUD Lalung Jaya, as the case study to be the self-supporting cooperation, has just reached the beginning steps. Therefore the participation of the members should be increase for the sake of its development.